Effects of modeling strategies for a slab track on predicted ground vibrations. Issue 136 (September 2020) - Malmborg, J.; Persson, P.; Persson, K.
Abstract: In the paper, the effect of modeling strategies regarding the dynamic behavior of a railway slab track on a layered half-space is studied. The track is modeled with various degrees of accuracy through the use of either beam theory, shell finite elements or solid finite elements. The underlying soil response is included through a dynamic stiffness, obtained via the Green's function for a horizontally layered visco-elastic half-space in the frequency–wavenumber domain. The effect of different assumptions regarding the track cross-section behavior and the track–soil interface conditions on the resulting free-field vibrations are studied for a harmonic load moving along the track. First, only the out-of-plane displacements of the slab–soil interface are coupled, i.e. only the vertical contact pressure is accounted for. Secondly, the effect of coupling the slab–soil in-plane displacements on the free-field vibrations is studied. It is found that the in-plane slab–soil coupling significantly affects the vertical vibration in the free-field. It is also found that a beam model of the track yields accurate response levels compared to a solid continuum model in the case of a thick slab, whereas considerable differences are obtained for a thin slab. Highlights: Prediction of train-induced ground vibrations. Comparison of semi-analytical beam model to shell and solid finite element models. Effect of in-plane coupling of slab—soil interface on predicted ground vibration. Cross-section flexibility significantly affects predicted vibrations for thin slabs. Beam model accurate for thick slabs with low cross-section flexibility.